Access to food and physical activity environment resources in rural communities: Impact of using driving time versus physical distance indicators. (December 2022) - Dixon, Brittney N.; Hong, Young-Rock; Perri, Michael G.; Allen, Acquel; Aufmuth, Joe; Ross, Kathryn M.
Abstract: Introduction: The one-mile buffer is commonly used in examining associations between the built environment and weight-related outcomes; however, this buffer may not adequately capture access to built environment resources among individuals residing in geographically dispersed rural communities. Thus, there is need to explore how different buffer sizes and types capture access to built environment resources in rural communities. Objective: This study compared two physical distance buffers (i.e., one-mile and two-mile) against two driving distances (i.e., 15-min and 30-min) to determine ability to capture access to built environment resources related to dietary intake and physical activity for participants in a weight management trial across rural counties. Methods: Data from the Rural Lifestyle Eating and Activity (Rural LEAP) trial were combined with publicly available geospatial datasets to identify and examine built environment resources for individuals residing in 13 rural counties in Florida. Descriptive statistics were calculated to determine access to built environment resources, and paired samples t-tests were used to compare access across various buffers and by level of rurality. Results: Results demonstrated limited resources available within the one- and two-mile buffers; however, participants had greater access to resources in the 15- and 30-min driving distances. Using supermarkets and grocery stores as an example, findings also demonstrated that participants residing in less rural counties compared to more rural counties had greater access to supermarkets and grocery stores within the 15-min (mean [SD] 9.16 [6.03], p < .0001) and 30-min (mean [SD] 24.82 [9.19], p = .007) driving distance buffers. There were no significant differences in the number of supermarkets between more or less rural counties for the one- and two-mile buffers. Conclusion: Driving distances may be useful measures to capture access to built environment resources in rural communities. Future studies should examine alternative buffers that adequately capture built environment resources accessed by rural residents. Highlights: Differences may exist in access to resources by level of rurality. Limited access to built environment resources in 1-mile and 2-mile buffers. Driving distance may better capture access to built environment resources.